VNTR markers for qualitative evaluation of engraftment in unrelated cord blood transplantations - Noor, S.M.; Phipps, M.E.; Fong, M.Y.; Chan, L.L. (2007)
Allogeneic stem cell transplantation is a treatment option for malignant and non-malignant disorders in children. For children with no HLA-matched sibling or related stem cell donors, there is the option of unrelated cord blood donors. At the University of Malaya Medical Centre (UMMC) in Kuala Lumpur, the first unrelated cord blood transplantation (CBT) was performed in October 1997. All unrelated CBT performed in UMMC relied on cord blood units imported from overseas. DNA typing with variable number of tandem repeat (VNTR) loci was done to qualitatively evaluate engraftment in 15 unrelated CBT. In all the fifteen cases that were evaluated, molecular evidence of engraftment or non-engraftment correlated with the clinical findings.